Analisis Perhitungan Harga Pokok Produksi Pada UMKM : (Studi Kasus Pada UMKM Sari Buah Blimbing Wuluh) - Lucia Putri Wulandari; Anifah Tiara Kusuma Wardani; Kafidin Muzakki (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Sari Buah Blimbing Wuluh MSMEs is one of the businesses engaged in food and beverage processing with the basic ingredients of star fruit. MSMEs Sari Buah Blimbing Wuluh has a problem in determining COGS which still uses the estimation method only. The purpose of this study was to identify the cost of production activities using the Full Cousting method. The method used in this research is deductive qualitative with data collection techniques through observation and interviews. The results showed that there was a price difference of Rp. 398 per bottle, with the calculation of COGS according to MSMEs amounting to Rp. 2,917 per bottle. While the calculation according to the full costing method is Rp. 3,315. This price difference occurs because business owners do not take into account direct labor costs, fixed factory overhead costs, variable costs, and non-production costs. So that the calculations made by MSMEs owners are not optimal for maximizing business profits.